Illuminating ‘second life’s benefits and challenges as an interactive blended virtual learning platform for English language teaching and learning - Hassan, Riad F.; Dzakiria, Hisham; M Idrus, Rozhan (UDEEEWANA, 2016)
The advancement and innovation on learning technology such as 3D virtual worlds offers new opportunities for teaching and learning languages. Learning English as a foreign language like many other foreign languages possess as a challenging task to teachers and students. Virtual World such as Second Life (SL) functions as a global platform potentially can become a powerful tool in learning and teaching of English as a foreign language due to its immersive and interactive environments. Its interactive interfaces provide students with realistic experiences and simulated everyday situation in 3D virtual worlds for more authentic and physical practice that would enhance students’ awareness of the target culture, knowledge construction and learning.This paper highlights the benefits and challenges associated with Second Life as an educational tool in EFL classroom.Specifically, this paper is intended to review Second Life potential in virtual learning and its affordances offerings to enhance EFL which produces the motivating factor towards a doctoral study on Second Life and its potential to offer a fun-engaging-inviting learning of the target language never envisioned or made possible in the conventional classrooms.